ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR MATEMATIKA SISWA: KAJIAN BERDASARKAN FAKTOR INTERNAL DAN EKSTERNAL - Suci Putri Warman; Neisya Anggraini; Nurul Aulia; Novferma; Husni Nabil (STKIP Subang, 2026)
This study aims to identify and analyze factors that cause students' difficulties in learning mathematics, viewed from both internal and external aspects. The instrument used was a Likert-scale mathematics learning difficulties questionnaire with 30 statements covering nine indicators. The number of respondents was 17 students. Data processing was carried out using the reverse scoring technique for negative items, where a higher score indicates a lower level of difficulty. The results of the analysis showed that the average total score of students was 111.47 out of an ideal maximum score of 150, indicating that the level of learning difficulties was generally in the low to moderate category. External factors, particularly the family environment (average 4.41) and facilities (average 4.35), were identified as the strongest supporting factors that minimized students' learning barriers. Conversely, the main sources of students' learning difficulties stemmed from the classroom environment (average 3.18), weaknesses in operational skills (average 3.26), and concentration and attention constraints (average 3.27).